DYNAMICS OF HUITLACOCHE HARVEST (Ustilago maydis Cda.) IN NINE COMMERCIAL CORN HYBRIDS - Clemente Villanueva Verduzco; Cuauhtémoc Escalante Pérez; Evert Villanueva Sánchez; Jaime Sahagún Castellanos; Irma Sánchez Cabrera (Tropical and Subtropical Agroecosystems, 2020)
Background. In contract farming, planned production is desirable. The planned artificial production of huitlacoche can be achieved by successive sowing dates to guarantee the continuous supply of the product throughout the year. Objective. To analyze the yield of huitlacoche and its harvest distribution through cutting in nine maize commercial hybrids. Methodology.  An experiment was carried out in a completely randomized design, with four replications in Chapingo State of México, México. Measurements of yield and quality (gall size) of the fungus were made in four cuts per hybrid during harvest. Results. In the nine hybrids studied, most of the harvest was concentrated in the second cutting. The Cronos and Dk-2042 hybrids (3,608 kg·ha-1 and 3,301 kg·ha-1, respectively) were the best in yield and quality of fungal galls and with contrasting distribution of their harvest. Implications. Hybrids Cronos and Dk-2042 can be used in an intensive and continuous production unit of huitlacoche. Cronos can be used to attend a daily demand of 1.5 t of fresh huitlacoche; while the Dk-2042 can be used to satisfy a weekly demand of 6 t, due to the respective overlaps of harvest among successive sowing dates. A surface of 14 ha is required, sowing 1 ha.week-1 of corn with a yield of 6 t.ha-1 to offer to the market 1.5 t.día-1 (Cronos hybrid) or 6 t.week-1 (Dk-2042 hybrid), depending on theirs contrasting distribution of the harvest among cutting. Conclusions. There are clear differences among the distribution of the harvested huitlacoche among commercial maize hybrids. The analysis of the yield per cutting allows to establish the varietal pattern of fungus harvest. Sequential plantings of complementary harvesting dynamics hybrids can be scheduled to serve continuous supply contracts.